Penguatan Reciprocal Teaching melalui Pengembangan Self-Efficacy Matematis pada Siswa Sekolah Dasar - Amelia, Reski; MS, Andi Trisnowali; Aspikal, Aspikal (Universitas Nusantara PGRI Kediri, 2025)
Mathematics learning at the elementary school level requires an appropriate approach to build students' conceptual understanding and self-efficacy. Based on observations, there is still a low level of mathematical ability and self-efficacy among students at SD Inpres Morowa, as evidenced by students' difficulties in understanding basic mathematical concepts, lack of active participation in learning, and low self-confidence in solving mathematical problems. Therefore, the purpose of this community service activity is to improve students' mathematical abilities through the implementation of reciprocal teaching reinforced with self-efficacy development. The method used is peer teaching with a collaborative approach involving 19 fourth-grade students. This activity was carried out in three stages: preparation, implementation, and evaluation. The results of this activity show a significant improvement in students' mathematical abilities and an increase in students' self-efficacy, as seen in the increased self-confidence, activeness, and ability to explain mathematical concepts to peers.